Social work and families in child welfare in Malawi: Social workers considerations when placing a child outside the home (Journal of Comparative Social Work, 2015)
This article discusses professional discretion in relation to placing a child outside the family, as understood by Malawian social workers. The article is a product of an exploratory study covering different aspects of social work practice with children and families in Malawi. It is based on focus group discussions with practicing social workers that were conducted using a vignette. This article describes how social workers handle child protection cases, in which a child has to be placed outside the home or family. The article points out different solutions and the reasoning behind certain decisions on placing children outside their home. The study explores issues of patriarchy, intervention methods into families and the cooperation between social workers, community members and other professionals when helping families. The study found that a number of different factors affect the decision of placing a child outside the home. Social workers in this study put an emphasis on the importance of helping children within the immediate- and extended family to help cope with the lack of financial resources that would provide alternative options.